The Interferon-Inducible Mouse Apolipoprotein L9 and Prohibitins Cooperate to Restrict Theiler’s Virus Replication - Kreit, Marguerite (PLoS One, 2015)
Apolipoprotein L9b (Apol9b) is an interferon-stimulated gene (ISG) that has antiviral activity and is weakly expressed in primary mouse neurons as compared to other cell types. Here, we show that both Apol9 isoforms (Apol9b and Apol9a) inhibit replication of Theiler’s murine encephalomyelitis virus (TMEV) but not replication of vesicular stomatitis virus (VSV), Murid herpesvirus-4 (MuHV-4), or infection by a lentiviral vector. Apol9 genes are strongly expressed in mouse liver and, to a lesser extent, in pancreas, adipose tissue and intestine. Their expression is increased by type I interferon and viral infection. In contrast to genuine apolipoproteins that are involved in lipid transport, ApoL9 has an intracytoplasmic localization and does not seem to be secreted. The cytoplasmic localization of ApoL9 is in line with the observation that ApoL9 inhibits the replication step of TMEV infection. In contrast to human ApoL6, ApoL9 did not sensitize cells to apoptosis, in spite of the presence of a conserved putative BH3 domain, required for antiviral activity. ApoL9a and b isoforms interact with cellular prohibitin 1 (Phb1) and prohibitin 2 (Phb2) and this interaction might contribute to ApoL9 antiviral activity. Knocking down Phb2 slightly increased TMEV replication, irrespective of ApoL9 overexpression. The antiviral activity of prohibitins against TMEV contrasts with the pro-viral activity of prohibitins observed for VSV and reported previously for Dengue 2 (DENV-2), Chikungunya (CHIKV) and influenza H5N1 viruses. ApoL9 is thus an example of ISG displaying a narrow antiviral range, which likely acts in complex with prohibitins to restrict TMEV replication.